Strategi Komunikasi TikTok @Triasmadani Dalam Meningkatkan Corporate Branding Di Kalangan Calon Pekerja Migran Indonesia - Winda Dwi Rahmawati (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This study examines the communication strategy of TikTok @triasmadani in enhancing the corporate branding of PT Trias Insan Madani among Prospective Indonesian Migrant Workers (CPMI). Using a descriptive qualitative method, this research analyzes the application of new media theory and Integrated Marketing Communication (IMC) strategy in the company’s TikTok content. The results show that PT Trias Insan Madani successfully utilizes TikTok as the main platform to improve corporate branding by presenting language learning, inspirational, and informative content. The company implements seven IMC elements – advertising, direct marketing, sales promotion, public relations, personal selling, social media marketing, and events- tailored to TikTok’s characteristics. This strategy aims to build trust among CPMI, deliver accurate information, educate prospective migrant workers, and enhance content creativity. The study concludes that PT Trias Insan Madani’s TikTok communication strategy is effective in improving corporate branding and receives positive responses from CPMI.